Customer relationship management: Are software applications aligned with business objectives? - M. L. Hart (South African Journal of Business Management, 2006)
Customer relationship management (CRM) can be thought of as IT-enabled relationship marketing. It has numerous definitions and perspectives, and success of implementation has been limited to date. This paper examines recent literature on the subject, drawing attention to the importance of a balance between strategy formulation, IT and organisational alignment when adopting and implementing CRM. It then discusses results of an exploratory study carried out amongst 34 South African organisations on their business objectives for CRM, the CRM applications that they have invested in or are considering, and the extent of integration of their customer data. The most important objectives and most widely used CRM applications are determined, and associations between applications and objectives are analysed. It is not apparent that CRM applications are selected in line with business objectives, and expected associations with objectives often do not exist for the objectives rated most important. Only certain aspects of customer data integration are significantly linked to objectives or CRM applications. The study suggests the need for fuller determination of strategy and objectives when involved with CRM investigation and adoption, and co-ordination at all levels of implementation between Marketing and IT.
Keywords: 650